2017
DOI: 10.14348/molcells.2017.0151
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Is Pro-Senescence When Seen in Close-Up, but Anti-Senescence in Long-Shot

Abstract: When mammalian cells and animals face a variety of internal or external stresses, they need to make homeostatic changes so as to cope with various stresses. To this end, mammalian cells are equipped with two critical stress responses, autophagy and cellular senescence. Autophagy and cellular senescence share a number of stimuli including telomere shortening, DNA damage, oncogenic stress and oxidative stress, suggesting their intimate relationship. Autophagy is originally thought to suppress cellular senescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 53 publications
0
54
0
1
Order By: Relevance
“…It is probably important to consider the difference between basal and stress-induced autophagy: A lack of the former would lead to the accumulation of damaged macromolecules (such as p62-containing aggresomes) and damaged organelles (such as dysfunctional mitochondria). Thus, it is conceivable that loss of basal autophagy alone promotes senescence through cellular damage (Kwon et al 2017). For instance, a role of basal autophagy in preventing senescence of muscle satellite cells, thus maintaining stemness, has been reported previously (García-Prat et al 2016).…”
Section: Autophagymentioning
confidence: 98%
See 1 more Smart Citation
“…It is probably important to consider the difference between basal and stress-induced autophagy: A lack of the former would lead to the accumulation of damaged macromolecules (such as p62-containing aggresomes) and damaged organelles (such as dysfunctional mitochondria). Thus, it is conceivable that loss of basal autophagy alone promotes senescence through cellular damage (Kwon et al 2017). For instance, a role of basal autophagy in preventing senescence of muscle satellite cells, thus maintaining stemness, has been reported previously (García-Prat et al 2016).…”
Section: Autophagymentioning
confidence: 98%
“…The positive regulation of senescence by autophagy was counterintuitive, considering the role of autophagy in cellular quality and fitness checks, although it is possible that increased autophagy activity serves as a prosurvival factor in senescent cells, which are known to be resistant to the cell death machinery (Dörr et al 2013). The relevance of autophagy in senescence appears to be highly context-dependent (Kwon et al 2017). It is probably important to consider the difference between basal and stress-induced autophagy: A lack of the former would lead to the accumulation of damaged macromolecules (such as p62-containing aggresomes) and damaged organelles (such as dysfunctional mitochondria).…”
Section: Autophagymentioning
confidence: 99%
“…Interestingly, recent studies disclosed distinct functions of general versus selective autophagy in the control of senescence, partially solving seemingly conflicting evidence concerning the relation between these two fundamental homeostatic responses to stress stimuli. In model cells other than MSCs, Kwon et al suggested the interesting possibility that such a dual role might be context and time dependent as well as specifically depend on the type of autophagy, general versus selective, involved (Kwon et al, 2017). According to this model, under normal conditions, general autophagy would act as an anti-senescence process by preserving cellular homeostasis.…”
Section: Reconciliationmentioning
confidence: 99%
“…However, general autophagy exerted in cells that have already initiated a senescence process can become prosenescent, in the sense that it can sustain viability of senescent cells. Indeed, senescent cells cannot dilute toxic byproducts as they do not undergo mitosis and they secrete a number of factors that can induce endoplasmic reticulum stress; in these conditions, autophagy induction could counteract the risk of proteostasis disruption and avoid cell death (Kwon et al, 2017). Accordingly, the anti-senescence autophagy roles reported above for MSCs were mainly related to general autophagy, and autophagy manipulation experiments were conducted before senescence induction.…”
Section: Reconciliationmentioning
confidence: 99%
“…Several studies have investigated the link between autophagy and senescence. In the context of stress-related senescence, it is thought that general autophagy prevents senescence, by counteracting cellular damage or stress that would trigger this response (Gewirtz, 2013;Kwon et al, 2017). For instance, in muscle satellite cells, autophagy prevents senescence in young muscle by opposing proteoxicity.…”
Section: Autophagymentioning
confidence: 99%